Local party organizations 1985 - Bjurulf, Bo; Håkansson, Anders (Lund University, 2025)
The study was conducted in connection with the 1985 general election and was based on a survey directed at local party organizations, specifically targeting the organizations’ chairpersons and campaign managers. The primary focus of the survey was on the parties’ local organization, activities, and political positions. Several questions were designed as a direct follow-up to the local democracy research group’s corresponding survey conducted during the 1979 election. In addition, the questionnaire included specific sections concerning election campaigns, campaign strategies, and perceived electoral outcomes.

Studien genomfördes i anslutning till riksdagsvalet 1985 och baserades på en enkätundersökning riktad till kommunala partiorganisationer, specifikt till organisationernas ordförande och valledare. Undersökningen fokuserade främst på partiernas lokala organisation, verksamhet och politiska ställningstaganden. En del av frågorna utgjorde en direkt uppföljning av den kommunaldemokratiska forskningsgruppens motsvarande studie i samband med valet 1979. Utöver detta innehöll enkäten särskilda avsnitt med fokus på valkampanjer, valstrategier och upplevda valresultat.
Kommunal partiorganisation 1985
Keywords: LOCAL GOVERNMENT ELECTIONS; KOMMUNALVAL; POLITICAL PARTIES; POLITISKA PARTIER; ELECTION CAMPAIGNS; VALKAMPANJER; Government, political systems and organisations; Regering, politiska system och organisationer; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap